(untitled) - Francis, Felix (New York, 2012)
"When race caller and television presenter Mark Shillingford calls a race in which his twin sister, Clare, an accomplished and successful jockey, comes in second when she could have won, he believes the worst: that she lost on purpose, and the race was fixed. That night, Mark confronts Clare with his suspicions, she storms off after an argument--and it's the last time Mark sees her alive. Hours later, Clare jumps to her death from the balcony of a London hotel; or so it seems. Devastated and guilty over her death, Mark goes in search of answers. What had led Clare to take her own life? Or was it not suicide at all? "--
Library Journal Prepub Alert
Publishers Weekly
Adult.
Adult.
Keywords: Fiction; England; Fiction; Horse racing; Fiction; Siblings; Mystery fiction; Fiction; Sportscasters; Women jockeys